Tecnologias inovadoras e processos consolidados em larga escala para produção de biogás: uma rota sustentável para destinação de resíduos sólidos urbanos no Brasil - Paula, Rafael de (Universidade Federal de São Carlos, 2022)
As urban centers and industry develop, global concern about climate issues associated with the high waste generation and use of non-renewable energy sources is also increasing. Brazil, as many other countries, still maintains unsustainable systems for the management and disposal of municipal solid waste (MSW), such as open dumps. Thus, it is extremely important to apply new improvements to overcome this scenario. Waste to energy processes have this purpose, once waste conversion to new energy resources become possible. In this process, the anaerobic digestion of organic matter gives bioenergy as product promoting the waste valorization. This work aims to perform a survey of scientific publications on the Web of Science platform with innovative technologies and large-scale consolidated process for biogas production through anaerobic digestion of MSW, in order to present sustainable destinations for MSW in Brazil. For this survey the 2020 year stood out with the largest number of publications, with China being the country that published the most. Articles publications correspond to 75% of the results, where environmental sciences have most publications. A more detailed analysis of some selected articles shows that 45% of them had a case study to present an implemented process and its main characteristics. Most of these selected studies (34%) operated large volumes of waste and were classified as large-scale. The plant with the highest production capacity produces 19525 m³/day of biogas in biodigesters that together add up to 2400 m³. Also, for these large-scale studies the main steps involved in the processes were identified, which consists of RSU reception, pre-treatment, anaerobic digestion, downstream and bioproduct destination.
Innovative technologies and large-scale consolidated processes for biogas production: a sustainable route for urban solid waste disposal in Brazil
Keywords: Digestão anaeróbia; Resíduos sólidos urbanos; Usina de biogás; Waste to energy; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL